2019
DOI: 10.18261/issn.2387-5984-2019-01-04
|View full text |Cite
|
Sign up to set email alerts
|

Medspill og motspill mellom profesjonene tilknyttethverdagsrehabilitering

Abstract: Kunnskapsgrunnlaget for hverdagsrehabilitering er økende, men vi vet ennå lite om det tverrprofesjonelle samarbeidet i tjenesten. Denne studiens hensikt er å utforske hvilke faktorer som bidrar til medspill og motspill mellom profesjoner tilknyttet hverdagsrehabilitering i Norge. Det empiriske datamaterialet baserer seg på deltakende observasjon, intervjuer og dokumentstudier. De faktorene som er identifisert til å skape medspill, er å vaere med på noe stort, tverrprofesjonalitet, profesjonell autonomi og flek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
(24 reference statements)
0
3
0
2
Order By: Relevance
“…Norwegian and Danish studies have shown that the philosophy of reablement can co-exist alongside pre-existing philosophies of care and this does not need to be a barrier to reablement delivery (Moe et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Norwegian and Danish studies have shown that the philosophy of reablement can co-exist alongside pre-existing philosophies of care and this does not need to be a barrier to reablement delivery (Moe et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…• Reablement is a person-centred, goal-directed intervention used to regain, maintain or improve the independence of older people • Community-dwelling older adults value reablement • Reablement fits with the dominating discourse around active ageing and the policy approach of health and social investment in wellness What the paper adds? • Provides an insight into a regional approach to reablement delivery within a single community-based organisation using a qualitative research approach than having these decided by a third party (Hjelle et al, 2018;Liaaen & Vik, 2019;Moe et al, 2019;Rostgaard, 2018;Smeets et al, 2020).…”
Section: What Is Known About the Topic?mentioning
confidence: 99%
See 1 more Smart Citation
“…Det verkar som samhandlinga i teamet er inspirerande og utviklande i form av kunnskapsheving. Informantane beskriv korleis dei laerer av kvarandre, noko som òg er vist tidlegare (Birkeland et al, 2017;Hjelle et al, 2018;Hjelle et al, 2016;C. F. Moe et al, 2019;Randström, Wengler, Asplund & Svedlund, 2014;K.…”
Section: Diskusjonunclassified
“…Vidare kan helsetenestene opplevast som separate siloar som ikkje samhandlar (Goodwin et al, 2017;Hellesø et al, 2019). For å få til god samhandling mellom ulike fagpersonar, vil det vere nyttig med kjennskap til faktorar som fremmar og hemmar samhandlinga (Kassah & Tønnessen, 2016;C. F. Moe et al, 2019).…”
Section: Introduksjonunclassified